Staphylococcus aureus Isolates from Goat and Sheep Milk Seem to Be Closely Related and Differ from Isolates Detected from Bovine Milk - Merz, Axel; Stephan, Roger; Johler, Sophia (Frontiers in Microbiology, 2016)
Dairy goat and sheep farms suffer severe economic losses due to intramammary infections, with Staphylococcus aureus representing the main cause of clinical mastitis in small ruminants. In addition, S. aureus contamination of goat and sheep milk may cause staphylococcal food poisoning, as many traditional caprine and ovine milk products are not subjected to pasteurization. Data on virulence and antimicrobial resistance genes, as well as on the clonality of S. aureus detected in goat and sheep milk is scarce. Therefore, it was the aim of this study to determine (i) spa types and clonal complexes (CC) and (ii) virulence and resistance gene profiles of S. aureus isolated from goat and sheep milk. A total of 162 milk samples from sheep and goats presenting signs of an intramammary infection and 104 bulk milk samples were collected. While low prevalence rates of S. aureus was detected on single animal level, 46% of the bulk tank milk samples from small ruminants were positive for S. aureus. All isolates were spa typed and CC and virulence and resistance gene patterns were determined using a DNA microarray. Data from 49 S. aureus isolates was included in the statistical analysis and the construction of a SplitsTree. The analyzed isolates could be assigned to eleven CC, with the large majority of goat and sheep isolates being assigned to CC130 and CC133. The findings of this study suggest that S. aureus shows pronounced adaptation to small ruminants in general, but not to sheep or goats in particular. Although some common characteristics among S. aureus from caprine, ovine, and bovine milk samples were observed, S. aureus from small ruminants seem to form a distinct population. As 67% of the detected S. aureus strains exhibited at least one enterotoxin gene, many caprine, or ovine raw milk products may be contaminated with low levels of enterotoxigenic S. aureus, stressing the importance of strict maintenance of the cold chain.